Technical-tactical profile, perceived exertion, mental demands and enjoyment of different tactical tasks and training regimes in basketball small-sided games - Sansone, Pierpaolo; Tessitore, Antonio; Lukonaitiene, Inga; Paulauskas, Henrikas; Tschan, Harald; Conte, Daniele (Biology of Sport, 2020)
This study aimed to evaluate the technical-tactical, perceptual and mental demands of basketball small-sided games (SSGs). Twelve male semi-professional players participated in four half-court 3vs3 SSGs characterized by different tactical tasks (offensive; defensive) and training regimes (long-intermittent; shortintermittent). The SSGs were video-recorded to perform notational analysis of technical-tactical parameters. Ratings of perceived exertion (RPE, CR-100 scale), mental effort (ME) and e njoyment were collected after completion of each SSG. Before and after the SSGs, players reported their perceived mental fatigue (MF); for this indicator, the difference between post- and pre-SSG values was calculated (ΔMF). Notational analysis evidenced a higher volume of play (ball possessions, ball possessions per minute) [large effect size (ES)], dribbles and shot attempts (moderate ES) in short-intermittent regimes compared to long-intermittent. Two-way (tactical task; training regime) repeated-measures ANOVA showed an interaction effect for RPE (moderate ES). Players reported that playing the offensive task required higher mental effort compared to playing defence (moderate ES), while no differences for mental effort were found between regimes. Enjoyment did not differ between tasks or regimes. No effects were found for ΔMF, while this indicator was significantly correlated with RPE scores (r= 0.50, large). This study suggests that, in basketball SSGs, shorter regimes induce higher technical demands, while tactical tasks influence perceived exertion responses and mental effort. Furthermore, perceived exertion appears significantly associated with variations of mental fatigue induced by training drills